Improvement in IBC-silicon solar cell performance by insertion of highly doped crystalline layer at heterojunction interfaces. (September 2017) - Bashiri, Hadi; Azim Karami, Mohammad; Mohammadnejad, Shahramm
Abstract : By inserting a thin highly doped crystalline silicon layer between the base region and amorphous silicon layer in an interdigitated back-contact (IBC) silicon solar cell, a new passivation layer is investigated. The passivation layer performance is characterized by numerical simulations. Moreover, the dependence of the output parameters of the solar cell on the additional layer parameters (doping concentration and thickness) is studied. By optimizing the additional passivation layer in terms of doping concentration and thickness, the power conversion efficiency could be improved by a factor of 2.5%, open circuit voltage is increased by 30 mV and the fill factor of the solar cell by 7.4%. The performance enhancement is achieved due to the decrease of recombination rate, a decrease in solar cell resistivity and improvement of field effect passivation at heterojunction interface. The above-mentioned results are compared with reported results of the same conventional interdigitated back-contact silicon solar cell structure. Furthermore, the effect of a-Si:H/c-Si interface defect density on IBC silicon solar cell parameters with a new passivation layer is studied. The additional passivation layer also reduces the sensitivity of output parameter of solar cell to interface defect density.